Ziriab: Arabic Music in the Czech Republic - Skořepová Honzlová, Zita (Lidé města, 2010)
With its four musicians of Syrian, Lebanese and Iraqi origin, Ziriab is the only and very first ensemble in the Czech Republic whose members declare their aim to be to perform “original” Arabic music. This idea of “original” Arabic music is a concept shared by the group, as has been articulated by the musicians. Their intentions have been expressed in relation to the character of the repertoire and its presentation. It is possible to depict four categories of performance – each one of a different context and audience type. The musicians’ choice of the repertoire as well as their behavior during the concert, then, reflect main aspects at each kind of performance. The founding members of the ensemble came from Syria to the former Czechoslovakia as exchange-program students in the ’80s and finally decided to stay in Prague as permanent residents. They mastered the Czech language and have fully integrated into the local society, as have the other two musicians from Lebanon and Iraq who joined the ensemble a few years later. Ziriab members’ opinions reveal the fact that their hobby of “dealing with Arabic music” arose during their several years of uninterrupted stay in the Czech Republic. As young men still living in their homeland, they never performed in public or studied music with a mentor’s guidance. This paper thus outlines specific conditions of the relationship between their long-term stay in a foreign country (and culture) and a need to perform music somehow related to the musicians’ – in this case ethnic and secular – identity.